Health workers' perceptions and challenges in implementing meningococcal serogroup a conjugate vaccine in the routine childhood immunization schedule in Burkina Faso - Sylvain F. Nkwenkeu; Mohamed F. Jalloh; Jenny A. Walldorf; Robert L. Zoma; Felix Tarbangdo; Soukeynatou Fall; Sansan Hien; Roland Combassere; Cesaire Ky; Ludovic Kambou; Alpha Oumar Diallo; Akshaya Krishnaswamy; et al. (BMC, 2020)
Abstract Background Meningococcal serogroup A conjugate vaccine (MACV) was introduced in 2017 into the routine childhood immunization schedule (at 15-18 months of age) in Burkina Faso to help reduce meningococcal meningitis burden. MACV was scheduled to be co-administered with the second dose of measles-containing vaccine (MCV2), a vaccine already in the national schedule. One year following the introduction of MACV, an assessment was conducted to qualitatively examine health workers' perceptions of MACV introduction, identify barriers to uptake, and explore opportunities to improve coverage. Methods Twelve in-depth interviews were conducted with different cadres of health workers in four purposively selected districts in Burkina Faso. Districts were selected to include urban and rural areas as well as high and low MCV2 coverage areas. Respondents included health workers at the following levels: regional health managers (n = 4), district health managers (n = 4), and frontline healthcare providers (n = 4). All interviews were recorded, transcribed, and thematically analyzed using qualitative content analysis. Results Four themes emerged around supply and health systems barriers, demand-related barriers, specific challenges related to MACV and MCV2 co-administration, and motivations and efforts to improve vaccination coverage. Supply and health systems barriers included aging cold chain equipment, staff shortages, overworked and poorly trained staff, insufficient supplies and financial resources, and challenges with implementing community outreach activities. Health workers largely viewed MACV introduction as a source of motivation for caregivers to bring their children for the 15- to 18-month visit. However, they also pointed to demand barriers, including cultural practices that sometimes discourage vaccination, misconceptions about vaccines, and religious beliefs. Challenges in co-administering MACV and MCV2 were mainly related to reluctance among health workers to open multi-dose vials unless enough children were present to avoid wastage. Conclusions To improve effective administration of vaccines in the second-year of life, adequate operational and programmatic planning, training, communication, and monitoring are necessary. Moreover, clear policy communication is needed to help ensure that health workers do not refrain from opening multi-dose vials for small numbers of children.